Composition and Intraspecific Variability in Summer Flounder (Paralichthys dentatus) Diets in a Eutrophic Estuary - Cernadas-Martín, Sara; Rountos, Konstantine J.; Nye, Janet A.; Frisk, Michael G.; Pikitch, Ellen K. (Frontiers in Marine Science, 2021)
This study assessed the diet of Summer flounder (SF, Paralichthys dentatus) in Shinnecock Bay, NY. Summer flounder are a recreationally and commercially important marine flatfish species found along the Eastern U.S. coastline. Despite their importance, few studies have examined the trophodynamics of a broad size spectrum of this species. Diet composition of summer flounder (n= 88) was assessed from 2014 to 2016 throughout Shinnecock Bay, a eutrophic bar-built estuary in New York. Species consumed and diet species richness differed significantly amongst SF size classes, with large (≥375 mm total length) and medium (>225:<375 mm) summer flounder showing higher levels of piscivory and more diverse diets than small-sized (≤225 mm) conspecifics. As voracious plastic predators, trends in annual and monthly diet variation generally followed prey availability in Shinnecock Bay. One exception to this general pattern occurred for winter flounder (Pseudopleuronectes americanus). Despite their low relative abundance in the bay, winter flounder was highly preferred as prey by summer flounder; (Chesson index, α= 0.35) and was their predominant prey item accounting for 12.3 % (s.d.±3.9%) of the diet by weight. Other factors that explained the variability of the diet of summer flounder were year, month, dissolved oxygen concentration, bay region and habitat, with a cumulative variance of 10.3 %. Interestingly, clear differences in the diet (i.e. species richness and abundance) of summer flounder were found within regions of Shinnecock Bay, with a decrease in teleost biomass and species richness observed in the western region where water quality is more degraded and less seagrass is available compared to the more pristine eastern region. Distinct trophic dynamics in degraded habitats suggests fundamentally different food webs that could have important consequences to ecosystem stability and resilience. As coastal areas continue to experience degradation, diet studies of economically and ecologically important species can aid in the development of effective ecosystem-based management plans.